Myxoid liposarcoma presenting like a cystic neck swelling - Sahni, Harmeet; Gautam, Raj; Lal, Vikash; Shaikh, Tanveer Parvez; Palshetkar, Karishma; Oak, Aditya (International Journal of Research in Medical Sciences, 2017)
Soft tissue sarcomas are rare and unusual neoplasm’s, accounting for approximately 1% of adult human cancers and 15% of pediatric malignancies. Most liposarcomas occur in deep soft tissues of the extremities and retroperitoneum; only a very small percentage (as low as 2%) occurs in the head and neck. Here we present a case of a 48yr old male with a painless mass in the neck clinically presenting as a cystic swelling. The CT neck was suggestive of cystic lesion in the neck representing benign cystic lesion. The swelling was excised and sent for histopathology which was suggestive of myxoid liposarcoma. The patient was planned for wide excision of the edges and scar and adjuvant chemo and radio therapy.